MANAGERIAL CONTROL OF RESOURCES AND INFRASTRUCTURAL FACILITIES AS CORRELATES OF STUDENTS' ACADEMIC ACHIEVEMENTS IN STATE COLLEGES OF EDUCATION IN SOUTHWESTERN NIGERIA (2012)
The demand for education in Nigeria has led to overcrowded classrooms as well as overstretched teachers and facilities. The social-economic instability, the standard of education in the country and the managerial control of resources have constituted major problems to students' academic achievement. This situation has become a national concern to all stakeholders. Prior studies have concentrated on availability and mobilisation of resources. In spite of several studies on availability and mobilisation of resources, the quality of products of tertiary education in Nigeria remains a subject of discourse. This study therefore examined the extent to which managerial control of resources (human, financial and material resources) and infrastructural facilities (transportation and accommodation) correlates with students' academic achievement in state colleges of Education in Southwestern, Nigeria. The study adopted the descriptive survey research design of the ex-post facto type. The stratified random sampling technique were used to select 600 students, 200 academic staff, 200 junior non-academic staff and 200 senior non-academic staff from six pioneer state colleges of education. Instruments used for the study are Managerial Control Inventory (Human, x ? =0.96), (Financial, x ? =0.75) and (Material, x ? =0.84) and Infrastructural Variables Inventory (Transportation, x ? =0.86) and (Accommodation, ?=0.94). These were complemented with data from the examinations and records departments in all the selected colleges. Seven research questions were answered and seven hypotheses tested at the 0.05 level of significance. Data were analysed using Pearson Product Moment Correlation and Multiple Regression. Managerial control of resources and infrastructural variables taken jointly correlates significantly with students' academic achievement and accounted for 44% of the variance of students' academic achievements. Relatively, the components of the managerial variable contributed to academic achievement in the following order: human resource (?=0.39, t=11.23, p<0.05) and financial resource (? =0.14, t=4.07, p<0.05). However, material resource did not make significant contribution to the prediction of academic achievement. Infrastructural facilities contributed to academic achievement in the following order: transportation (? =0.20, t=4.82, p<0.05) and accommodation (?=0.12, t=3.20, p<0.05). On the whole, the mean score of the students' examination results collected from the six selected colleges of education range was ( x ? =51.64). This value showed that the academic achievement of the selected colleges were on the average. Furthermore, the managerial variables (r=0.57) and infrastructural facilities (r=0.44) independently correlated significantly with students' academic achievement. Managerial control of resources and infrastructural facilities are critical factors in relations to academic achievement of students in colleges of education. The management of the colleges should ensure that the available resource - human, financial and material - are judiciously managed and the college authority should provide good hostel accommodation and effective transportation system for the use of the students. The management of colleges should ensure that college libraries operate for the use of students on weekends.